Automated lipid-rich plaque detection with short wavelength infra-red OCT system. (27th November 2017) - Shimokado, Aiko; Kubo, Takashi; Nishiguchi, Tsuyoshi; Katayama, Yosuke; Taruya, Akira; Ohta, Shingo; Kashiwagi, Manabu; Shimamura, Kunihiro; Kuroi, Akio; Kameyama, Takeyoshi; Shiono, Yasutsugu; Yamano, Takashi; et al.
Abstract: Aims: Vulnerable coronary plaque is characterized by a large lipid core. Although commercially-available optical coherence tomography (OCT) systems use near-infrared light at 1300 nm wavelength, lipid shows characteristic absorption at 1700 nm. Therefore, we developed a novel, short wavelength infra-red, spectroscopic, spectral-domain OCT. The aim of the present study is to evaluate the accuracy of short wavelength (1700 nm) infra-red optical coherence tomography (SWIR-OCT) for identification of lipid tissue within coronary plaques. Methods and results: Twenty-three coronary arteries from 10 cadavers were imaged at physiological pressure with 2.7 Fr SWIR-OCT catheter. When a blood-free image was observed, the SWIR-OCT imaging core was withdrawn at a rate of 20 mm/s using an automatic pullback device. SWIR-OCT images were acquired at 94 frames/s and digitally archived. SWIR-OCT generated grey-scale cross sectional images and colour tissue maps of all of the plaque by using a lipid analysis algorithm. After SWIR-OCT imaging, the arteries were pressure-fixed, sliced by cryostat and stained with Oil Red O, and then corresponding histology was collected in matched images. Regions of interest, selected from histology, were 117 lipidic and 34 fibrotic/calcified regions. SWIR-OCT showed high sensitivity (89%) and specificity (92%) for identifying lipid tissue within coronary plaques. The positive predictive value and negative predictive value were 97% and 74%, respectively. Conclusion: SWIR-OCT accurately identified lipid tissue in coronary autopsy specimens. This new technique may hold promise for identifying histopathological features of coronary plaque at risk for rupture.